Let history into the mathematics classroom. (2018) - Barbin, E (Evelyne); Guichard, Jean-Paul; Moyon, Marc, 1976-; Guyot, Patrick; Morice-Singh, Catherine; Métin, Frédéric; Bühler, Martine; Tournés, Dominique; Chorlay, Renaud; Hamon, Gérard
No abstract available